Analysis of Implementation and Optimization of Carbon Mitigation Mechanisms in Oil and Gas Industry Using Multi-Criteria Decision Analysis - Luthfiyah Revi Sukmasari*; Gunawan Nugroho (Universitas Syiah Kuala, 2024)
Indonesia signed the Paris Agreement in 2016, thus actively contributing to tackling climate change has an obligation to reduce greenhouse gas (GHG) emissions. The main factor of global climate change is the increase of GHG, especially carbon dioxide (CO2) and methane (CH4). PT X is committed to supporting Net Zero Emission 2060 by encouraging programs that have a good impact on the environment and Sustainable Development Goals (SDG's) 13 and supporting the government in handling the climate crisis. The ranking of alternatives is carried out using two structured methods, quantitative analysis using Analytic Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), considering environmental, economic, and social aspects. used to help make decisions for the implementation of carbon mitigation mechanisms. From the observation of the previous implementation, carbon emissions in the production process were quite high. So it is necessary to make effective carbon mitigation efforts. There are three criteria that influence action decisions, namely environmental criteria, economic criteria and social criteria. The results of the weight value of each criterion are that the environment has the highest weight (0.61), followed by economic criteria (0.20) and social criteria (0.19) from these values indicate that environmental criteria are the most important criteria in decision making. The ranking results show that the Piston Modification Program and the Diesel Engine to Gas Engine Replacement Program are optimal options for short-term implementation. The Carbon Capture and Storage (CCS) program should be considered for long-term investment, with the potential for large emission reductions and long-term cost savings.